Analysis of toxic effects of Alternaria toxins on esophagus of mice by light and electron microscopy - Yekeler, H; Bitmis, K; Özçelik, N; Doymaz, MZ; Çalta, M (Taylor & Francis Inc, 2001)
In this study, the possible toxic effects of Alternariol Methyl Ether (AME) and Tenuazonic Acid (TeA) produced by Alternaria species on esophagus of mice were investigated by using light and electron microscopy techniques. Mice were orally fed daily with AME or TeA for 10 months and at the end of this period, the effects of these chemicals on the esophageal mucosa were determined. By light microscopic examination, moderate and severe dysplasia characterized by loss of polarity, nuclear pleomorphism, and hyperchromasia were observed in TeA-treated animals. Electron-microscopic examination of TeA-treated mucosal epithelial cells revealed pyknosis in some nuclei, granulation and increase in chromatin mass, irregularities in the nuclear contours, vacuolization in nucleoplasms, and marked pleomorphism in the nuclei. In conclusion, our results suggested that TeA has higher toxicity as evidenced by dysplastic transformation.
Keywords: alternariol methyl ether; histopathology; mycotoxin; tenuazonic acid